Need of booster vaccine doses to counteract the emergence of SARS-CoV-2 variants in the context of the Omicron variant and increasing COVID-19 cases: An update - Ranjan K. Mohapatra; Nahed A. El-Shall; Ruchi Tiwari; Firzan Nainu; Venkataramana Kandi; Ashish K. Sarangi; Teroj Abdulrahman Mohammed; Perumal Arumugam Desingu; Chiranjib Chakraborty; Kuldeep Dhama (Taylor & Francis Group, 2022)
The emergence of different variants of SARS-CoV-2, including the Omicron (B.1.1.529) variant in November 2021, has resulted in a continuous major health concern at a global scale. Presently, the Omicron variant has spread very rapidly worldwide within a short time period. As the most mutated variant of SARS-CoV-2, Omicron has instilled serious uncertainties on the effectiveness of humoral adaptive immunity generated by COVID-19 vaccination or an active viral infection as well as the protection provided by antibody-based immunotherapies. Amidst such high public health concerns, the need to carry out booster vaccination has been emphasized. Current evidence reveals the importance of incorporating booster vaccination using several vaccine platforms, such as viral vector- and mRNA-based vaccines, as well as other platforms that are under explorative investigations. Further research is being conducted to assess the effectiveness and durability of protection provided by booster COVID-19 vaccination against Omicron and other SARS-CoV-2 variants.